miR-24-3p/FGFR3 Signaling as a Novel Axis Is Involved in Epithelial-Mesenchymal Transition and Regulates Lung Adenocarcinoma Progression - Pengyu Jing; Nan Zhao; Nianlin Xie; Mingxiang Ye; Yong Zhang; Zhipei Zhang; Mengyang Li; Xiaofeng Lai; Jian Zhang; Zhongping Gu (Journal of Immunology Research)
Our previous studies showed that Fibroblast growth factor receptor 3 (FGFR3) contributed to cell growth in lung cancer. However, the correlation between FGFR3 and tumor progression, coupled with the underlying mechanisms, are not fully understood. The clinical significance of FGFR3 was determined in two cohorts of clinical samples (n=22, n=78). A panel of biochemical assays and functional experiments was utilized to elucidate the underlying mechanisms and effects of FGFR3 and miR-24-3p on lung adenocarcinoma progression. Upregulated FGFR3 expression indicated an adverse prognosis for lung adenocarcinoma individuals and promoted metastatic potential of lung adenocarcinoma cells. Owing to the direct regulation towards FGFR3, miR-24-3p could interfere with the potential of proliferation, migration, and invasion in lung adenocarcinoma, following variations of EMT-related protein expression. As a significant marker of EMT, E-cadherin was negatively correlated with FGFR3, of which ectopic overexpression could neutralize the antitumour effects of miR-24-3p and reverse its regulatory effects on EMT markers. Taken together, these findings define a novel insight into the miR-24-3p/FGFR3 signaling axis in regulating lung adenocarcinoma progression and suggest that targeting the miR-24-3p/FGFR3 axis could be an effective and efficient way to prevent tumor progression.